2015
DOI: 10.1007/s00429-015-1065-0
|View full text |Cite
|
Sign up to set email alerts
|

Homotopic reciprocal functional connectivity between anterior human insulae

Abstract: The aim of this study was to investigate functional connectivity between right and left insulae in the human brain. We studied a patient with implanted depth electrodes for epilepsy surgery evaluation with stereotactically placed symmetric depth electrodes in both insulae. Bipolar 1 Hz electrical stimulation of the right and left posterior short gyri in the anterior insula evoked responses in the contralateral insular structures. These responses showed a latency of 8-24 ms. This report demonstrates for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…33 The SEEG investigations of insular lobe seizures have shown the following: (1) Seizure onset patterns can be variable in the insula, but low-voltage fast discharge 34 or high-frequency gamma activity 7 are not uncommon (Figure 3B and C); (2) seizures often start very focally with a limited intrainsular spread before extrainsular propagation (Figure 3B-D), which therefore allows tailored limited resections (Figure 3E) 35 ; (3) extrainsular spread explains clinical variability of insular lobe seizures; in particular, complex motor manifestations were shown to occur when the discharge spread over frontomesial and/or mesial and lateral temporal regions. 16 This is in accordance with directed functional coupling analysis that reported a specific association between the insula and mesial frontal lobe during the propagation of insular seizures 34 ; (4) corticocortical evoked potentials have showed that the 2 insulas are closely connected, 36 with 8- to 24-milliseconds time to propagate from one to the other homotopic insular parcel 37 ; therefore, insular seizures may propagate very quickly to the contralateral insula (Figure 3B) so that false lateralization may occur in insular or even temporo(-insular) epilepsy 38 ; (5) typical insular signs can occur in seizures of extrainsular origin; in particular, insular spread is very common in seizures of temporal lobe origin 22,39 and therefore may result in misleading seizure auras; and (6) the morbidity rate directly related to insular electrodes is low. In particular, none of the patients (including children) reported in 3 recent large studies experienced any hemorrhagic complications.…”
Section: Invasive Recordings Of Insular Lobe Seizuressupporting
confidence: 85%
“…33 The SEEG investigations of insular lobe seizures have shown the following: (1) Seizure onset patterns can be variable in the insula, but low-voltage fast discharge 34 or high-frequency gamma activity 7 are not uncommon (Figure 3B and C); (2) seizures often start very focally with a limited intrainsular spread before extrainsular propagation (Figure 3B-D), which therefore allows tailored limited resections (Figure 3E) 35 ; (3) extrainsular spread explains clinical variability of insular lobe seizures; in particular, complex motor manifestations were shown to occur when the discharge spread over frontomesial and/or mesial and lateral temporal regions. 16 This is in accordance with directed functional coupling analysis that reported a specific association between the insula and mesial frontal lobe during the propagation of insular seizures 34 ; (4) corticocortical evoked potentials have showed that the 2 insulas are closely connected, 36 with 8- to 24-milliseconds time to propagate from one to the other homotopic insular parcel 37 ; therefore, insular seizures may propagate very quickly to the contralateral insula (Figure 3B) so that false lateralization may occur in insular or even temporo(-insular) epilepsy 38 ; (5) typical insular signs can occur in seizures of extrainsular origin; in particular, insular spread is very common in seizures of temporal lobe origin 22,39 and therefore may result in misleading seizure auras; and (6) the morbidity rate directly related to insular electrodes is low. In particular, none of the patients (including children) reported in 3 recent large studies experienced any hemorrhagic complications.…”
Section: Invasive Recordings Of Insular Lobe Seizuressupporting
confidence: 85%
“…In some circumstances, the rat posterior insula shows no lateralization of cardiovascular function in response to stimulation ( 90 ); while differences between rat and humans ( 74 ) may extend to lateralization, these recent data, nevertheless, show that the insula has complex topographic organizational and different response patterns arise from different stimulation types. The two hemispheres also show strong connections in the anterior insula ( 99 ). Nevertheless, human stroke findings are consistent with a right-sided sympathetic regulatory role ( 28 , 100 , 101 ).…”
Section: Discussionmentioning
confidence: 99%
“…28 There is no paninsular spread, and contralateral insula involvement is very fast. Corticocortical evoked potentials demonstrate both insulas are closely connected, 30 with 8to 24-millisecond propagation time between homotopic insular parcels 31 ; therefore, early contralateral insula propagation may lead to false lateralization.…”
Section: Insular Seizures Start Focally With Limited Intrainsular Spreadmentioning
confidence: 99%